Does Conditionality Mitigate the Potential Negative Effect of Aid on Revenues? - Crivelli, Ernesto (IMF Working Papers; Working Paper ;, 2016)
This paper assesses whether conditionality in IMF-supported programs has helped offset the potential negative effect of foreign aid on tax revenues. The analysis-carried out on panel data covering 1993-2012 for 111 low- and middle-income countries-shows that growing use of revenue conditionality by low-income countries partially offsets the depressing effect of foreign grants on tax revenue, particularly on taxes on goods and services. The impact of conditionality is strong in countries where aid dependence is high and where institutions are strong, suggesting that revenue conditionality cannot substitute for weak institutions in mitigating the negative effect of aid on tax revenue collection.